Personality Type and Learning Style Preferences as Determinants of Students’ Achievement in Senior Secondary School Biology in Osun State, Nigeria (2014)
Poor performance of students in biology at the senior secondary school level over the years has raised a serious concern among stakeholders particularly in Osun State. This trend has been attributed generally to factors relating to the home, school and the students themselves. Previous studies have neglected personality type and learning style preferences in relation to students‟ achievement in Biology. Therefore, this study examined through path linkages how personality type and learning style preferences determine students‟ achievement in biology at the senior secondary school (SSS) level in Osun State, Nigeria. The study adopted the survey research design.This study was based on the Myers-Briggs, and Dun and Dun models that characterised personality type on: Extroversion, Sensing, Thinking, Judging (ESTJ), and learning style on: Visual, Auditory, Kinesthetic (VAK) respectively. The multistage sampling technique was used to select 1,480 SSS II students from 74 senior secondary schools in 15 selected local government areas. Three instruments were used: Cognitive Type Inventory (r=0.52), VAK Learning Style Indicators (r=0.65), Biology Achievement Test (r=0.75). Four research questions were answered. Pearson product moment, Path analysis, and Multiple regression were used to establish and estimate direct and indirect hypothesised linkages at 0.05 level of significance. The percentage of respondents with different personality type preferences were: extroversion (62.3%), sensing (66.3%), thinking (63.3%), judging (63.1%), and that of learning style preferences were: visual (63.0%), auditory (78.1%), kinesthetic (35.8%). The predictor variables had significant correlations with students‟ achievement as: student gender (-0.074), extroversion (-0.269), sensing (-0.417), thinking (0.376), judging (0.327), visual (-0.430), auditory (-0.408), Kinesthetic (-0.438). The discrepancy between hypothesised and reproduced correlations in the model was minimal (26.7%). Five hypothesised predictor variables [student age (-0.058), extroversion (-0.113), sensing (-0.284), thinking (0.109), and kinesthetic (-0.347)] had direct effects on biology achievement. On the other hand, only three hypothesised predictor variables [student gender (-0.017), student age (0.011), and thinking (0.064)] had indirect effects on biology achievement. The percentages of direct and indirect paths were 15.4% and 84.6% respectively. About 27.9% of the variance observed in biology achievement was accounted for by age, extroversion, sensing, thinking, and kinesthetic. Sensing and kinesthetic preferences were the most significant in determining students‟ achievement in biology at the sampled senior secondary schools in Osun State. Students should be encouraged to develop, improve and exhibit sensing and kinesthetic preferences when learning biology